La desigualdad sociogeográfica en la prevalencia de anemia en niños - Pari Olarte, Josefa Berta (2024)
Background: Anemia in children is a major public health problem in the world and Perú, especially in those under three years old. Aim: The study was designed to identify the social determinants that explain the socio-geographic inequality in the distribution of anemia prevalence in six-to-35-month Peruvian children. Methods: An observational, ecological, and analytic study was carried out in 26 subnational governments of Peru. Correlation tests, simple and multiple linear regression, and calculating inequality gaps and gradients were applied. Results: The proportion of pregnant women without iron supplementation was the only explanatory variable for the prevalence of anemia in children under 36 months. The absolute gradient of inequality reflected a pattern of equity (ICI = 0.02). Excess of anemia prevalence in six-to-35-month children was equivalent to 11.53% along the gradient determined by the proportion of pregnant women without iron supplementation. Territories in the quintile with the highest proportion of pregnant women without iron supplementation had the highest gap in absolute and relative terms (18.49% and 1.46%; respectively). Conclusions: The proportion of pregnant women without iron supplementation would explain the socio-geographic inequality gap in the prevalence of anemia in 6-to-35-month Peruvian children. In other words, territories with the lowest achievement of this indicator would be exposed to a higher prevalence of anemia, so universal interventions must be focused on them.